2010
DOI: 10.1002/btpr.389
|View full text |Cite
|
Sign up to set email alerts
|

Alternating current electric field effects on neural stem cell viability and differentiation

Abstract: Methods utilizing stem cells hold tremendous promise for tissue engineering applications; however, many issues must be worked out before these therapies can be routinely applied. Utilization of external cues for preimplantation expansion and differentiation offers a potentially viable approach to the use of stem cells in tissue engineering. The studies reported here focus on the response of murine neural stem cells encapsulated in alginate hydrogel beads to alternating current electric fields. Cell viability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 38 publications
0
34
1
1
Order By: Relevance
“…Cell numbers in all culture groups, including the controls, tended to decrease over time, and, although these changes were significant from 3 to 7 and 14 DIV in the 50-Hz treatment group, they were still not significantly different from the controls. These findings are in contrast to another study in which 1-Hz AC EFs significantly increased numbers of mouse NPCs (Matos and Cicerone, 2010). There could be many reasons for the difference in 1-Hz results between these two studies.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Cell numbers in all culture groups, including the controls, tended to decrease over time, and, although these changes were significant from 3 to 7 and 14 DIV in the 50-Hz treatment group, they were still not significantly different from the controls. These findings are in contrast to another study in which 1-Hz AC EFs significantly increased numbers of mouse NPCs (Matos and Cicerone, 2010). There could be many reasons for the difference in 1-Hz results between these two studies.…”
Section: Discussioncontrasting
confidence: 55%
“…There could be many reasons for the difference in 1-Hz results between these two studies. The previous group used a cell suspension in alginate that was subjected to an EF that varied from 2 to 16 V over the alginate-embedded cultures (Matos and Cicerone, 2010). Thus, they used a higher minimum field that also had a gradient, and the cells were within a gel matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric fields are known to be related to the neuronal differentiation of embryonic, neural and mesenchymal stem cells 4,25,42,45 . It is possible that the differentiation process can take place also when stimulating cells with electric field only but the upregulation of beta-tubulin isotype III, a marker for immature neurons, was seen only after 14 days of culture, compared to 4 days when using electric field and copper together.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the electric field stimulation of neuronal pre-differentiated embryonic stem cells remarkably increases their differentiation 45 . In addition, Matos et al reported the different effects of alternating electric fields, which were applied through nickel electrodes, on neural stem cell viability and differentiation 25 . They showed that neuronal differentiation was either enhanced or suppressed depending on the electric field frequency and the exposure time.…”
Section: Introductionmentioning
confidence: 99%